Effect of photoperiod on growth and flowering of curcuma alismatifolia Gagnep. - R. Changjeraja (2018)
Growth and flowering of C. alismatifolia Gagnep. growing in different photoperiod was studied at Chiang Mai University during January to July 2006. Plants were grown at 6, 10 and 14 h of light duration in growth chamber (Conther phytotron climate simulator) under 70-80% RH and 28±1°C. Light intensity was kept constantly at 270 μmol PPF (photosynthetieally photon flux). The experimental design was completely randomized design with ten replications. The result showed that plant grown at 6 h of day length was tall and slim. Plant height was 69.4 cm and leaf length was 42 cm, however leaf area was not significantly different from plants grown at 14 h. Photoperiod did not significantly affect the number of leaves per plant, leaf width and leaf color. Dry weight of leaves and fibrous roots were also greatest in plants growing at 14 h. The plant grown at 14 h has not formed new storage roots yet at flowering stage (8 weeks after planting), while the plants grown at 6 and 10 h have formed new storage roots with 7.65-8.03 gDW/plant. Flowering percentage was lowered under 6- and 10-h photoperiod (20 and 30%, respectively, compared with those under 14 h (100%). Number of coma bracts and the spike length of plants grown at 10 and 14 h were higher than plants grown at 6 h. The photoperiod did not significantly affect the number of green bracts and flower stalk length.